KAJIAN EMPIRIS HUBUNGAN KAUSALITAS PRAKTIK PELAPORAN KEUANGAN BASIS INTERNET (INTERNET FINANCIAL REPORTING) TERHADAP NILAI PERUSAHAAN DENGAN GCG SEBAGAI VARIABEL INTERVENING PADA 100 PERUSAHAAN TERKEMUKA DI INDONESIA - Isworo Wulandari; Emrinaldi Nur DP; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The aims of this research is to examine the direct effect and indirect effect of voluntary disclosure on the internet and age of firm on the GCG mechanisms consist of managerial ownership and independent commissioner. Collecting data using a purposive sampling method for 100 companies listed in Kompas-100 Index in 2013 which analyse by path analysis. The result show that: (1) Voluntary disclosure and firm’s age does not directly affect managerial ownership but both of the variables have a direct effect on independent commissioner, (2) Voluntary disclosure, firm’s age, firm’s size, industry sector and independent commissioner has a direct effect on the firm value, (3) Voluntary disclosure and firm’s age does not have a indirect effect on the firm value through the percentage of independent commissioner.Keywords: IFR, GCG, Voluntary, Size and Age